2013
DOI: 10.1093/treephys/tpt043
|View full text |Cite
|
Sign up to set email alerts
|

Growth of mature boreal Norway spruce was not affected by elevated [CO2] and/or air temperature unless nutrient availability was improved

Abstract: The growth responses of mature Norway spruce (Picea abies (L.) Karst.) trees exposed to elevated [CO(2)] (CE; 670-700 ppm) and long-term optimized nutrient availability or elevated air temperature (TE; ±3.9 °C) were studied in situ in northern Sweden in two 3 year field experiments using 12 whole-tree chambers in ca. 40-year-old forest. The first experiment (Exp. I) studied the interactions between CE and nutrient availability and the second (Exp. II) between CE and TE. It should be noted that only air tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 61 publications
8
111
0
1
Order By: Relevance
“…Due to interaction effects between temperature and SQ, the increase becomes more pronounced with increasing site quality. This results are congruent with Sigurdsson et al (2013), who found that the effect of temperature or CO 2 increases on mature Norway spruce in the boreal zone was not evident unless nutrient availability was improved. Our results are also consistent with Pretzsch et al's (2014) findings that growth acceleration, likely due to climate change, for Norway spruce since 1960 in Central Europe is stronger in more fertile sites.…”
Section: Spruce Dominatedsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to interaction effects between temperature and SQ, the increase becomes more pronounced with increasing site quality. This results are congruent with Sigurdsson et al (2013), who found that the effect of temperature or CO 2 increases on mature Norway spruce in the boreal zone was not evident unless nutrient availability was improved. Our results are also consistent with Pretzsch et al's (2014) findings that growth acceleration, likely due to climate change, for Norway spruce since 1960 in Central Europe is stronger in more fertile sites.…”
Section: Spruce Dominatedsupporting
confidence: 91%
“…One should be careful when applying these models to already established stands, as the climate-growth response of the stands already established might depend on the provenance, age, and elevation of the trees, among other factors (Primicia et al 2015). Productivity might also be affected by other factors that might change with time and that are not considered here such as CO 2 , nitrogen deposition (Sigurdsson et al 2013), nutrient availability, and solar radiation.…”
Section: Spruce Dominatedmentioning
confidence: 99%
“…Thus, since 1900, forests in Sweden have seen important changes in forest structure and composition (Antonson and Jansson, 2011). For this purpose, we used a former application of the Budyko framework (Jaramillo andDestouni, 2014, 2015;van der Velde et al, 2014) to study movement of basins in the space comprising the aridity index and the evaporative ratio, known as the Budyko space. We separated the climatic effect on evapotranspiration that relates to changes in the aridity index from a residual effect that relates to other drivers of change.…”
Section: F Jaramillo Et Al: Dominant Effect Of Increasing Forest Bimentioning
confidence: 99%
“…Nitrogen enhances both photosynthesis (Roberntz 2001) and growth (Sigurdsson et al 2013) and is one of the most limiting long-scale factors for growth in the boreal zone (Tamm 1991). Optimal nitrogen treatment may increase growth many-fold compared to controls (Bergh et al 1999).…”
Section: Carbon Balance Of a Treementioning
confidence: 99%
“…Furthermore, photosynthesis has been shown to increase with increasing CO2 levels and temperature (Uddling andWallin 2012, Wallin et al 2013). In spite of increased photosynthesis additional nitrogen is needed to achieve a positive response of growth for elevated CO2 and temperature levels (Sigurdsson et al 2013). Leuzinger et al (2013) succeeded in improving the biomass estimation of a dynamic global vegetation model by estimating tree growth with a sink-limited instead of source-limited model.…”
Section: Sink and Source Theoriesmentioning
confidence: 99%